Molecular characterization of the fibrinogen-erythrocyte interaction as a cardiovascular risk - Guedes, Ana Filipa (2017)
Tese de doutoramento, Ciências Biomédicas (Bioquímica Médica), Universidade de Lisboa, Faculdade de Medicina, 2018